The influence of NaCl and CaCl2 induced high temperature corrosion on the aqueous corrosion resistance of stainless steels. Issue 6 (20th February 2019) - Mori, Gregor; Vidic, Karl J.; Bucher, Edith; Yasir, Muhammad; Hornauer, Daniel; Nachtnebel, Manfred; Fitzek, Harald; Schroettner, Hartmuth
Abstract : The corrosion resistance of the steel grades 1.4509 and 1.4301 against sodium and calcium chloride, at 650 and 750 °C is investigated by means of cyclic exposure tests (CETs) in dry air. The formation of chromates as well as volatile metal chlorides and oxychlorides leads to non‐protective oxide scales on both steel grades. At 650 and 750 °C and in presence of a salt layer the alloy 1.4301 shows a higher corrosion resistance than the material 1.4509. At 750 °C and in presence of salt, the surface of the steel grade 1.4301 is transformed from a face centered cubic (fcc) to a body centered cubic (bcc) lattice, due to corrosion induced de‐alloying. The surfaces of both tested materials deplete in chromium, especially at 750 °C. Consequently, the corrosion resistance of the materials exposed to CET decreases sharply in aqueous corrodants. Abstract : The corrosion resistance of the steel grades 1.4509 and 1.4301 against sodium and calcium chloride, at 650 and 750 °C is investigated by means of cyclic exposure tests (CETs) in dry air. The formation of chromates as well as volatile metal chlorides and oxychlorides leads to non‐protective oxide scales on both steel grades. The surfaces of both tested materials deplete in chromium, especially at 750 °C.